Exploiting Feature Space Manipulation for Image Generation in Deep Convolutional Generative Adversarial Networks - Yang, Yujie (Transactions on Computer Science and Intelligent Systems Research, 2024)
Image generation and manipulation are important research directions in the field of computer vision and graphics. Traditional methods of image generation and manipulation often necessitate substantial manual intervention or are constrained by the quality and diversity of the dataset, leading to a lack of authenticity and control in the images produced. This paper provides an extensive examination of image generation and manipulation using Deep Convolutional Generative Adversarial Networks (DCGAN) and feature weighting operations. The model successfully captured the basic structure of a face. Furthermore, the color and texture of the images are quite realistic, indicating that the model has learned some basic features of the face. In terms of feature weighting operations, specific features are successfully transferred from one image to another. This research contributes valuable insights to the field of computer vision and graphics and paves the way for future advancements in image generation and manipulation. Ethical considerations and efficient training methods are also discussed as important aspects for future research.